Organic selenium supplement partially alleviated diquat-induced oxidative insults and hepatic metabolic stress in nursery pigs. Issue 1 (14th July 2020) - Doan, Nicole; Liu, Yanhong; Xiong, Xia; Kim, Kwangwook; Wu, Zhaohai; Bravo, David M.; Blanchard, Alexandra; Ji, Peng
Abstract: The study investigated antioxidant effects of Se on resilience to diquat-induced oxidative stress in nursery pigs. Thirty-five weaned pigs were individually housed and randomly assigned to one of the five treatments. Pigs were (1) fed a basal diet and intraperitoneally injected with sterile saline (negative control), (2) fed the basal diet and injected with diquat solution (positive control, PC), or fed the basal diet supplemented with 0·3 mg Se/kg as (3) sodium selenite (SS), (4) soyabean protein-chelated Se (SC) or (5) selenised yeast (SY) and intraperitoneally injected with diquat. Pigs were fed the experimental diets for 17 d and injected with diquat at 10 mg/kg body weight or saline on the 11th day of the study (day 0 post-injection (PI)). Diquat exposure induced acute stress and innate immune activation ( P < 0·05) at 6 h PI and compromised ( P < 0·05) plasma glutathione peroxidase activity on day 2 PI, which was accompanied by an increase in plasma malondialdehyde at 6 h and day 2 PI ( P < 0·10). Organic Se, particularly SY, enhanced ( P < 0·05) endogenous antioxidant activity in various aspects compared with the PC group. The growth rate and feed intake from day 0 to day 7 PI were significantly lower in the PC, SS and SC groups than the NC group ( P < 0·05). Untargeted metabolomics analysis revealed that twenty-two hepatic metabolites (false discovery rate < 0·15) associated with lipid and cellular antioxidant metabolism were altered by diquat. SY restored hepatic metabolic profiles in some but not all samples.